Model Strategi Pemberdayaan Ekonomi Rakyat sebagai Upaya Pengentasan Kemiskinan - Prasetyo, P. Eko; Maisaroh, Siti (Jurnal Trikonomika, 2009)
The aim of social and economy development are the same on the basic, that is to create prosperity for people, although the angle of view and approach can different. The People economy empowering as an effort to overcome poverty is economic development that is as well as social development. The aim of this article is to analyze the problem. The result of research shows that poverty is a one of serious social problems. Strategic model of peopleâs economy empowering is only one of the best approach from economic side. The strategic model will be better if combine with approaching from another politic, culture, social-economy side. The result point that poverty arise coused by the existence of difference in capital and nature resource awnership also the lack quality of human resource. It means, that a poor society is poor because it is poor. Because of that, strategic model of peopleâs economy empowering by the reinforcement of local recource potencial is one of the best and fast strategy that can be utilized to overcome poverty.